SYNTHESIS AND BIOLOGICAL EVALUATION OF SPIRO (INDOLE-THIAZOLIDINE) DERIVATIVES AS ANTIMICROBIAL AGENTS - SHINDE, PRIYANKA NIVRUTTI; RASKAR, MANISH ASHOK (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present study aims to synthesize and biological evaluation of Spiro-[Indole-Thiazolidine] derivatives as antimicrobial agents. Methods: The reaction sequence involves microwave-induced preparation of N-(2-oxo-1,2-dihydro-3’H-indol-3-ylidene)pyridine-4-carbohydrazide [3] from isoniazid [1] and isatin [2] followed by the cyclo condensation of [3] and mercaptoacetic acid under microwave condition to achieve the synthesis of spiro-[indole-thiazolidine] derivatives [4]. The resulting compounds were then allowed to react with various aromatic and heterocyclic aromatic aldehydes to afford arylidene derivatives [5a-l]. Result: Isoniazid (1) on condensation with isatin (2) in the presence of catalytic amount of glacial acetic acid furnished N-(2-oxo-1,2-dihydro-3’H-indol-3-ylidene) pyridine-4-carbohydrazide (3), which showed characteristic IR, absorption bands. Compound (3) underwent Spiro cyclization upon its reaction with mercaptoacetic acid in the presence of anhydrous ZnCl2 to form spiro-[indole-thiazolidine] compound (4). Compound (4) was then condensed with aromatic aldehydes to give arylidene derivatives (5a-l), which were characterized by IR and 1H NMR spectral data. Conclusion: All the synthesized compounds were screened for antimicrobial activity by the cup plate method. Most of the derivatives showed good antimicrobial activity against Gram-Positive and Gram-negative bacteria.